Using blended learning with the help of google classroom and whatsapp in learning of solid substance physics - Hamid, Abdul; Wahyuni, Sri (Edu Sains: Jurnal Pendidikan Sains & Matematika, 2023)
This study aims to determine the effect of blended learning assisted by Google Classroom and WhatsApp on students' cognitive abilities in solid substance physics lectures. This research is pre-experimental research with a one-group pretest-posttest design. The research sample was 30 students who were taken with the probability sampling technique. Data collection was done using tests and non-tests. The data analysis technique used was descriptive statistics. The analysis showed that students' cognitive abilities reached good criteria, with an average pretest score of 40.13. In contrast, students' cognitive skills on the posttest amounted to 71.17, with an average n-gain of 0.52. The results of student responses to the implementation of blended learning assisted by Google Classroom and WhatsApp, most students gave a positive response; this can be seen from the acquisition of an average percentage value of 73.30%.